The portrayal of older persons in grade 3 primary school children’s textbooks in Zimbabwe - Chipo Hungwe; Zvenyika Eckson Mugari; Elda Hungwe (Taylor and Francis Group, 2023)
This paper employs textual analysis to explain how older adults are depicted in children’s textbooks at primary school with specific focus on grade 3 level which is the beginning of Junior school at primary level. Because these textbooks are studied throughout the country, this discussion provides a picture of the national situation in so far as depiction of older people is concerned at junior stage in Zimbabwe. Contrary to the educational aims of the new school curriculum which seeks to inculcate values of respect, empathy and tolerance for diversity, older people are depicted as ‘needy’ and vulnerable, vestiges of the past living in rural areas. Older women fare worse than older men; they are almost invisible in children’s school textbooks due to ‘gendered ageism.’ The ageism in these books is reflective of the national discourse and overall paints a negative picture of older adults. This is not the way to prepare children and the nation for population aging.